OVERVIEW OF THE IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY (K3) FILING UNIT AT MITRA SEHAT SITUBONDO HOSPITAL - Ansyori, Anis; Bulgis, Malikal; Putri, Maria Meilani Alda (HEARTY, 2025)
The purpose of this study is to evaluate the implementation of electronic medical records (EMR) and occupational health and safety (OHS) at the filling unit of Mitra Sehat Situbondo Hospital. The research employed a qualitative descriptive method involving interviews and observations over a period of four months. Findings indicate that despite the hospital's adoption of EMR for outpatient care since May 2024, several departments and inpatient units still utilize conventional medical records. The filling unit faces challenges such as limited space and file stacking. The health of staff is affected by inadequate use of personal protective equipment (PPE). Nonetheless, the document disposal process has been effectively conducted to maintain confidentiality. This study underscores the need for infrastructure improvements and OHS practices to enhance efficiency and safety in the storage and handling of medical records at the hospital.